Land tenure security for women: A conceptual framework - Doss, Cheryl R.; Meinzen-Dick, Ruth S. (Elsevier, 2020)
While strengthening women’s land rights is increasingly on national and international agendas, there is little consensus on how to understand women’s tenure security. Analyses of women’s land rights often use very different definitions of land rights, from formal ownership to women’s management of plots allocated to them by their husbands. This paper identifies aspects of women’s tenure that should be included in indicators. It then provides a conceptual framework to identify the various dimensions of women’s land tenure security and the myriad factors that may influence it. To be able to compare women’s tenure security in different places, we need information on the context, the threats and opportunities facing tenure security, and the action arena that includes both the people who play a role in promoting or limiting women’s tenure security and the resources used in doing so.